Improving Drinking Water Management Efficiency in Batu City Water Utility with System Dynamics Modelling Approach - Arief, Amalia Mardhatillah; Siswoyo, Hari; Andawayanti, Ussy (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2024)
The increasing demand for drinking water due to population growth presents significant challenges for the Among Tirto Water Utility (ATWU) in Batu City, East Java, Indonesia. In 2022, ATWU faced low service coverage (36%) and high water loss (38%), exceeding the 20% threshold. Some previous research discusses the System Dynamics (SD) used to overcome the water shortage problem. In this study, the SD is used to overcome excess water. Therefore, This study aims to enhance efficiency by adding piping networks and controlling water losses. This research uses an SD approach method that includes simulations from 2017 to 2042 or for 25 years using the Powersim application. Methodologies include analyzing drinking water availability, constructing causal loop diagrams (CLD) and stock and flow diagrams (SFD), verification, validation, and designing policy scenarios. The required data are the number of customers, service coverage, actual production capacity, water loss, total community water consumption, business revenue, business expenses, and other data related to water management in ATWU. The study identifies Scenario Two as the most effective in addressing location-specific issues. If water loss control is implemented to reduce loss rates to 20%, ATWU could expand service coverage by 58.44%, increasing water availability and a projected profit of 3.6 billion rupiahs by 2042. The results of this study can improve operational efficiency and facilitate better decision-making for the Water Utility of Batu City.